(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2023)
In the process of writing this article, I reflected on my experience of the transformation of Ireland from an avowedly theocratic state, to one that has been the first in the world to vote for marriage equality by a margin of two to one. In addition, Leo Varadkar, the current Taoiseach, that is, Prime Minister, is openly gay, and his father was from India. Further, five years ago, in 2018, Ireland voted by 66.4% to 33.6% with a turnout of almost 65% to delete an anti-abortion clause in the Constitution of Ireland following a long and arduous campaign (Fitzsimons, 2021).